Swedish adult education policy and the world of work - Erik Nylander; Kjell Rubenson (European Journal for Research on the Education and Learning of Adults)
Public policies in adult education have been shaped by two generations of human capital influence, each reflecting different assumptions about the relationship between education and the economy. While the first generation, emerging in the post-war decades, has received little scholarly critique, the second has faced extensive criticism for its neoliberal orientation. Tracing these lines of thought internationally, we emphasise the need for a broader historical-institutional perspective to understand what was at stake and why the world of work remains a central component of contemporary Adult Learning and Education (ALE) policy. Using historical institutionalism and the concept of pressure points, we analyse Swedish adult education policy from the late 1950s onward. We show how its adult education system, shaped by both economic and social demands, emerged and has remained largely intact despite grand societal changes and political shifts. At the same time, evolving policies have paved the way for private providers within welfare services, hybridising the Swedish welfare-state-model.